2007
DOI: 10.1108/01409170710736329
|View full text |Cite
|
Sign up to set email alerts
|

Strategic decision‐making in the healthcare industry: the effects of physician executives on decision outcomes

Abstract: Purpose -Research on strategic decision-making has emphasized the importance of team decisionmaking as it brings the benefits of synergy. Literature on healthcare is silent on the role of professional doctors in the strategic decision-making process and their impact on decision outcomes. The purpose of the present paper is to empirically examine the outcomes of decisions when physician executives were involved in strategic decision-making process in healthcare organizations. Design/methodology/approach -Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
(42 reference statements)
0
5
0
2
Order By: Relevance
“…Two studies reported on doctors’ involvement in strategic decision-making. 37 38 Parayitam et al 37 examined the self-reported outcomes of decisions when physician executives were involved in strategic decision-making processes in 109 USA hospitals. Hypotheses were that increased numbers of doctors involved in strategic decision-making teams would be associated with better decisions, greater understanding of the rationale of decisions and more commitment to decisions.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on doctors’ involvement in strategic decision-making. 37 38 Parayitam et al 37 examined the self-reported outcomes of decisions when physician executives were involved in strategic decision-making processes in 109 USA hospitals. Hypotheses were that increased numbers of doctors involved in strategic decision-making teams would be associated with better decisions, greater understanding of the rationale of decisions and more commitment to decisions.…”
Section: Resultsmentioning
confidence: 99%
“…fulltime versus part-time) was positively associated with an increase in staff-to-patient ratios (nurse and physician) (Kuntz and Scholtes, 2013). Parayitam et al (2007) found that physician leadership participation was associated with higher-quality decision-making (e.g. with regard to coverage of a range of relevant issues, structured decision rationale, and securing commitment to decision implementation).…”
Section: Work Demands and Rewardsmentioning
confidence: 99%
“…There is a vital need for increased involvement of physicians in: (a) policy -especially in the areas of quality and clinical innovation, payment policy and medical education and training (Laugesen and Rice 2003); and (b) strategic and higher-order operational decisions in healthcare systems, as it affects commitment and the decision quality (Parayitam et al 2007). This requires that strong, value-based and assertive physician leaders become key partners with other healthcare leaders (Zismer and Brueggemann 2010).…”
Section: Affirming Versus Enabling Leadershipmentioning
confidence: 99%